A Research Study on the priorities for Sustainable innovation for the future of the Indian IT Industry and the impact on CSR (global social impact) - et. al., Vivek Arunachalam, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The research studies on the priorities for the Government to invest to create an ecosystem for the Indian IT Industry to help innovate and build a value chain to build sustainability in the competitive environment. Since India has emerged to be the most competitive nation with the Information technology sector, it is very important to innovate to build in an era when industrie 4.0 is taking shape post the new normal. The paper studies how the rise of industrial growth could support the role of corporate social responsibility thereby improvising the global social impact.